Portuguese as heritage language in Germany - a linguistic perspective - Rinke, Esther (2021)
This article provides a comprehensive overview of the contribution of linguistic research on Portuguese as a heritage language in Germany to the general understanding of heritage language development. From 1955 to 1973, nearly 166,000 Portuguese migrants found work in Germany as so-called ‘guest workers’ (Gastarbeiter). Because the aim of many Portuguese migrant families was to return to Portugal, their children met relatively good conditions for the acquisition of their heritage language. Nonetheless, second-generation heritage speakers (HSs) show some linguistic particularities in comparison to monolingual Portuguese speakers in Portugal. Based on the results of previous research, we show that the following factors shape the linguistic knowledge of this group of bilinguals: (1) Restricted exposure to the heritage language may cause a delay in the development of certain linguistic structures, (2) deviations from the standard norm may be related to the lack of formal education and the primacy of the colloquial register and (3) heritage bilinguals may accelerate ongoing diachronic development. We argue that apparent effects of influence from the environmental language can often have alternative explanations.